1993
DOI: 10.1016/0014-5793(93)80044-u
|View full text |Cite
|
Sign up to set email alerts
|

TGMV replication protein AL1 preferentially binds to single‐stranded DNA from the common region

Abstract: The AL1 protein of tomato golden mosaic virus (TGMV) is encoded by the viral DNA and has been shown to be essential for viral DNA replication. We have over-expressed the AL1 open reading frame in E. coli and purified the protein from bacterial extracts to near homogeneity. Using various different techniques we have studied the interaction of the AL1 protein with DNA. The AL1 protein is able to bind to DNA containing the common region of the viral genome, which can be demonstrated by photochemical cross-linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
4
17
1
Order By: Relevance
“…Although ACMV AC1 binding has not yet been investigated, the simplest interpretation of these data is that the N-terminal portion of AC1 interacts with sequences within domain A to suppress AC1 expression. The idea is consistent with reports describing the specific binding of ALl of TGMV and bean golden mosaic virus to sequences within the common region equivalent to domain A (Fontes et al, 1992(Fontes et al, , 1994aTh6mmes et al, 1993). A more detailed analysis of the TGMV ALl binding site and its involvement in transcriptional repression has identified a 13 bp element as a high affinity binding site, located nine nucleotides upstream of the ALl transcription start point (Fontes et aI., 1994b;Eagle et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…Although ACMV AC1 binding has not yet been investigated, the simplest interpretation of these data is that the N-terminal portion of AC1 interacts with sequences within domain A to suppress AC1 expression. The idea is consistent with reports describing the specific binding of ALl of TGMV and bean golden mosaic virus to sequences within the common region equivalent to domain A (Fontes et al, 1992(Fontes et al, , 1994aTh6mmes et al, 1993). A more detailed analysis of the TGMV ALl binding site and its involvement in transcriptional repression has identified a 13 bp element as a high affinity binding site, located nine nucleotides upstream of the ALl transcription start point (Fontes et aI., 1994b;Eagle et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…lanes 2 to 4 and lanes 6 to 8), indicating that AL1 binds to ssDNA in a sequence-nonspecific manner. Our result contrasts with an earlier study (70) that concluded that AL1 binds preferentially to a ssDNA sequence corresponding to TGMV common region based on binding to larger probes containing the entire common region (CR in Fig. S2A in the supplemental material).…”
Section: Vol 85 2011 Novel Motif Conserved Across Geminivirus Rep Pcontrasting
confidence: 99%
“…The radiolabeled band has an apparent molecular mass of 23 kDa, which is slightly larger than the protein itself, a condition which is most likely caused by the addition of oligonucleotides to the polypeptide upon cross-linking. Similar size shifts were observed for other DNA binding proteins, including the large subunit of dRP-A (14) and the tomato golden mosaic virus protein AL1 (21).…”
Section: Purification Of Dm Mtssbsupporting
confidence: 70%